Bionomics and management of root mealybug on black pepper - Najitha Ummer (Department of Agricultural Entomology, College of Horticulture, 2016)
Mealybugs are one of the important pests of black pepper and a specific group called as ‘root mealybugs’ are known to infest the underground parts of the crop in Kerala. The infestation was reported to be serious in high altitude region. Hence, an investigation was carried out on the “Bionomics and management of root mealybug on black pepper” with the objectives to document the species of root mealybugs and associated fauna, to study the biology of the dominant species, susceptibility of popular pepper varieties to the pest and management of mealybug on black pepper. The present study was conducted in the College of Horticulture and farmer’s fields at Wayanad and Idukki districts, Kerala. A preliminary survey was conducted during 2013 in different panchayats of Wayanad, Idukki and Kannur districts of Kerala to document the root mealybug species infesting black pepper. No infestation was observed in Kannur district, while three species of mealybugs, namely, Formicococcus polysperes Williams, Dysmicoccus brevipes Cockerell and Pseudococcus sp. were found to be infesting the underground parts of black pepper in Wayanad and Idukki districts.The collateral hosts of F. polysperes, recorded were two intercrops in pepper garden viz., ginger, Zingiber officinale Rose. and elephant foot yam, Amorphophallus paeoniifolius (Dennst.), and weeds, Ageratum conyzoides L., Clerodendron infortunatum L., Cyperus kyllinga L., Phyllanthus niruri L., Physalis minima L., Synedrella nodiflora L.,Urtica parviflora Roxb. and a pepper standard, Erythrina sp. The collateral hosts of D. brevipes were Coffea robusta L., Commelina diffusa L. Cleome rutidosperma (DC.) and C. kyllinga L. The infestation of F. polysperes on ginger is the first report from South India and its other hosts are being reported for the first time globally. During the survey, a coccinellid grub was observed to be predating on the root mealybugs which was identified as Horniolus sp. (Coccinellidae: Coleoptera). Four ant species viz., Anoplolepis gracilipes Smith, Crematogaster rogenhoferi Mayr, Lophomyrmex quadrispinosus Jerdon and Paratrechina sp. were also found to be associated with root mealybug colonies.The study on population dynamics of root mealybugs showed that the highest root mealybug population was in cooler months (November to January) and lowest population in rainy months (June and July). A significant negative correlation existed between root mealybug population and soil temperature. The biology and morphometrics of F. polysperes, were studied in laboratory condition in which females exhibited ovoviviparity mode of reproduction with pre larviposition, larviposition and post larviposition period of 23.65, 9.60 and 4.15 days, respectively. An adult female deposited an average of 136.15 crawlers with a sex ratio of 1: 2.71 (male: female). Life cycle of females consisted of three nymphal instars and adult and that of males had two nymphal, a pre-pupal, a pupal instar and an adult instar. Average duration of first and second nymphal instars was 8.4 and 6.35 days, respectively. Males and females were distinguishable from third instar onwards with a fine silken waxy thread formed by males at the end of second instar. Duration of third female instar was 8.4 days and that of pre-pupa and pupa of male was 1.4 and 7.15 days, respectively. Adult females are apterous with white powdery waxy coating and wax filaments surrounding the body margin are short and thick. Males are winged with a pair of long waxy caudal filaments. Males are short lived with an average life span of 1.8 days and females lived for 37.4 days. The biology of F. polysperes is being reported for the first time. Four popular pepper varieties, namely, Panniyur- 1, Panniyur- 2, Panniyur- 8 and Karimunda were tested for their susceptibility to root mealybugs and Panniyur- 2 was found to be most susceptible and recorded significantly higher number of mealybugs on artificial inoculation. Entomopathogenic fungi (EPF), chemical insecticides and their combinations were evaluated for the management of root mealybugs on black pepper. Four species of entomopathogenic fungi were tested at three different concentrations each and out of which, Lecanicillium lecanii at 2 x 108 spores/ml was found effective under both laboratory and pot experiment. Out of the eight insecticides evaluated against root mealybugs, chlorpyriphos 20 EC at 300 g a.i/ha and imidacloprid 17.8 SL at 25 g a.i/ha were equally superior in laboratory tests whereas, imidacloprid 17.8 SL at 25 g a.i/ha was the most effective in pot culture experiment. Compatibility test of L. lecanii with pesticides indicated that imidacloprid 17.8 SL (25 g a.i/ha) and copper hydroxide 77 WP (1%) was compatible with respect to per cent growth inhibition, sporulation and spore viability. The best treatments of EPF and chemical insecticides were evaluated alone and in combinations, with common farmer’s management practice in pot experiment and the result showed that imidacloprid 17.8 SL at 25 g a.i/ha was effective in managing root mealybugs and the same was evaluated in an infested field at Wayanad and compared with chlorpyriphos 20 EC @ 300 g a.i/ha. The results showed that imidacloprid 17.8 SL @ 25 g a.i/ ha was superior with 97.98 per cent reduction in population at one week after first drenching when compared to that of chlorpyriphos (79.89 per cent).